2018
DOI: 10.3390/w10060695
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the Wettability and Water Storage Capacity of Common Oak Leaves (Quercus robur L.)

Abstract: Abstract:The canopy water storage capacity and wettability of the plant material are significantly dependent on the condition of the leaf surface. The aim of the present research was an analysis of the influence of infection with oak powdery mildew, seasonal changes occurring on leaves and factors related to location on the surface of leaves and their hydrological properties. This study performed a series of experiments connecting the direct spraying of tree branches with simulated rainfall under laboratory co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…A significantly higher stemflow during the leafless rather than in the leafed period was observed also in other studies (André et al, 2008;Šraj et al, 2008;Zabret et al, 2017;Zabret and Šraj, 2019). However, leaf wettability and water storage capacity are also varying with seasons (Klamareus-Iwan and Witek, 2018). Additionally, Iida et al (2017) showed that not only the phenophase but also the length of the event and its period (i.e., the first and the second half of the event development) influenced the response of stemflow.…”
Section: Introductionsupporting
confidence: 77%
“…A significantly higher stemflow during the leafless rather than in the leafed period was observed also in other studies (André et al, 2008;Šraj et al, 2008;Zabret et al, 2017;Zabret and Šraj, 2019). However, leaf wettability and water storage capacity are also varying with seasons (Klamareus-Iwan and Witek, 2018). Additionally, Iida et al (2017) showed that not only the phenophase but also the length of the event and its period (i.e., the first and the second half of the event development) influenced the response of stemflow.…”
Section: Introductionsupporting
confidence: 77%
“…Growth strategies and physiology determine leaf life span [45,46], so it is reasonable to hypothesize that these attributes differ between species and will impact throughfall. Additionally, coatings on leaf surfaces change throughout the growing season, such that leaf hydrophobicity decreases as leaves age, increasing interception storage capacity, thus reducing throughfall [47]. Had this study been able to sample at shorter-time intervals, differences in phenoseasons beyond leaf-on vs. leaf-off canopy phase may have been expressed more strongly and led to periods during the year when throughfall was even more different among species.…”
Section: Discussionmentioning
confidence: 99%
“…It can be inferred that the more fragmented leaf and higher stem density (Table 2) are the dominant contributors to the smaller throughfall depth. Compared with a more compact leaf, a fragmented leaf enhances water adhesion capacity [11], which promotes surface evaporation due to a large wet surface area [15], by preventing the formation of large droplets [29] and generating smaller droplets by splashing. Smaller droplets evaporate quickly and reduces throughfall [31].…”
Section: Effect Of Plant Morphology On Ecohydrological Behaviormentioning
confidence: 99%
“…In addition, exploring the role plant morphology traits play is of particular importance in interpreting the variation of interception storage capacities among ecosystems [7]. Firstly, plant morphology traits affect the capacity of the canopy to intercept rainfall [11,[14][15][16]. For example, small, light, soft, and noncircular leaves, densely situated on small branches, have more effective water adhesion capacity [11].…”
Section: Introductionmentioning
confidence: 99%